2008
DOI: 10.1523/jneurosci.5298-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Modes of Network Homeostasis in Visual Cortical Layer 2/3

Abstract: Sensory experience is crucial for shaping the cortical microcircuit during development and is thought to modify network function through several forms of Hebbian and homeostatic plasticity. Where and when these different forms of plasticity are expressed at particular synapse types within cortical microcircuits, and how they interact, is poorly understood. Here we investigated how two different visual deprivation paradigms, lid suture (LS) and intraocular TTX, affect the local microcircuit within layer 2/3 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
344
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(376 citation statements)
references
References 43 publications
30
344
1
1
Order By: Relevance
“…In contrast, mEPSP frequency decreased strongly after 3 d of MD in WT mice but returned to baseline levels after 6 d of MD. The initial decrease in mEPSP frequency is in agreement with a previous study (32), which showed that 3 d of monocular lid suture decreased mEPSC frequency by 33% in the monocular zone. Moreover, it suggests that release probability decreased during the first 3 d of MD, consistent with the previously reported presynaptic LTD mechanism for closedeye depression (16).…”
Section: Synaptic Mechanisms That May Underlie Ocular Dominance Plastsupporting
confidence: 92%
“…In contrast, mEPSP frequency decreased strongly after 3 d of MD in WT mice but returned to baseline levels after 6 d of MD. The initial decrease in mEPSP frequency is in agreement with a previous study (32), which showed that 3 d of monocular lid suture decreased mEPSC frequency by 33% in the monocular zone. Moreover, it suggests that release probability decreased during the first 3 d of MD, consistent with the previously reported presynaptic LTD mechanism for closedeye depression (16).…”
Section: Synaptic Mechanisms That May Underlie Ocular Dominance Plastsupporting
confidence: 92%
“…Intraocular TTX injection, lid suture, and dark rearing lead to a wide range of distinct changes in strengths of local connections among neurons in layers IV and II/III and in the intrinsic properties of those neurons in the monocular zone of the rat visual cortex before and at the beginning of the critical period (32,33). These changes do not account for the delayed plasticity of the visual responses of inhibitory neurons that we find in the binocular cortex in vivo.…”
Section: Discussioncontrasting
confidence: 53%
“…Control (unmanipulated) animals were imaged at ages that spanned the critical period (postnatal days [25][26][27][28][29][30][31][32][33][34][35]. Imaging sessions began with intrinsic signal mapping of the binocular zone to locate the binocular portion of the primary visual cortex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of sensory deprivation on STP is often inconsistent even for the same synapse type, with specific types of sensory deprivation promoting facilitation but others increasing depression [31 •• , [39][40][41][42][43]. A number of experimental factors, including the nature and age of deprivation [39,44] Similarly, preNMDARs influence STP at synapses from L4 neurons onto L2/3 pyramidal neurons, but not at L2/3 intralaminar synapses [47]. Development and sensory experience regulate pre-NMDAR expression, suggesting that these receptors are well suited for regulating synapse-type-specific STP [31 •• , 33,39,48].…”
Section: Synapse-type-specific Short-term Plasticitymentioning
confidence: 99%